GE_GERICHTE P/15811/2015 vom 6. Dezember 2016 - GE Cour de justice (2016)
IN DUBIO PRO REO; SÉJOUR ILLÉGAL; CONFISCATION(DROIT PÉNAL); DÉLIT CONTINU; INDEMNITÉ(EN GÉNÉRAL) | LETR.115.1.B OASA.A.1 LETR.10 CP.70.1 CPP.429.1.A CPP.429.1.C